Planning Lessons for Arabic Teachers in the Primary Stage Using Artificial Intelligence Techniques - Hassan, Haifa Hamid; dawood, Noor alhuda noor aldeen (Journal of Ecohumanism, 2025)
The current study aimed to know "lesson planning for Arabic language teachers in the primary stage using artificial intelligence techniques"To verify the objective of the study, the researchers chose the descriptive approach, and the sample was chosen randomly stratified. To build the paragraphs of the questionnaire, the researchers conducted an exploratory study on a number of randomly selected teachers, and reviewed the relevant literature.The paragraphs of the questionnaire reached 84 standards definitively, and the results were summarized in general to the existence of a significant weakness plans lessons for Arabic language teachers for the primary stage, and the alternatives to the paragraphs of the scale were five-point, and as follows (not mastered, slightly mastered, well mastered, excellent). When the saw to result, the researcher propose recommendations for using artificial intelligence applications to solve the problem of plans, including: Training Arabic language teachers on how to plan lessons, especially the daily plan in light of artificial intelligence applications.Issuing an educational booklet on how to prepare plans and how to organize each of the Arabic language plans from artificial intelligence programs.Issuing an educational booklet on how to prepare plans and how to organize each of the Arabic language plans from artificial intelligence programs.To complement the current study, the researchers propose to conduct several studies, including:A study similar to the current study is the study of middle and middle school teachers.The impact of training workshops to develop teachers in artificial intelligence applications in planning their lessons.